2001
DOI: 10.1023/a:1019546617485
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Primary membranoproliferative glomerulonephritis (MPGN) has a poor long-term prognosis, with 40 per cent of patients reaching end-stage renal failure after 10 years of observation. Approximately 35 per cent of patients die due to complications of the nephrotic syndrome. This study investigates the effect of acetylsalicylic acid (ASA) combined with dipyridamole on proteinuria and renal function in nephrotic MPGN patients with normal/moderately reduced glomerular filtration rate (GFR). Fourteen patients with bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In two meta-analyses of antiplatelet therapy for IgA nephropathy, dipyridamole therapy was beneficial for reducing the risk of proteinuria [ 27 , 28 ]. In addition, dipyridamole combination therapy with ACE-I, antiplatelet agents or immunosuppressants significantly reduced proteinuria in patients with IgA nephropathy and primary membranoproliferative glomerulonephritis [ 18 , 19 , 29 , 30 ]. However, our knowledge about the reno-protective effect of dipyridamole use is limited in pre-dialysis, advanced CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two meta-analyses of antiplatelet therapy for IgA nephropathy, dipyridamole therapy was beneficial for reducing the risk of proteinuria [ 27 , 28 ]. In addition, dipyridamole combination therapy with ACE-I, antiplatelet agents or immunosuppressants significantly reduced proteinuria in patients with IgA nephropathy and primary membranoproliferative glomerulonephritis [ 18 , 19 , 29 , 30 ]. However, our knowledge about the reno-protective effect of dipyridamole use is limited in pre-dialysis, advanced CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dipyridamole stimulates nitric oxide action and inhibits platelet aggregation via the inhibition of phosphodiesterase and has an antioxidant effect [ 14 – 16 ]. A number of clinical studies have shown the reno-protective effects of dipyridamole monotherapy or combination therapy with ACEIs, antiplatelet agents or immunosuppressants in the treatment of early CKD in patients with diabetic kidney disease, IgA nephropathy, and membranoproliferative glomerulonephritis [ 17 – 19 ]. However, studies focusing on dipyridamole monotherapy or its interaction with RAAS blockade in patients with CKD 5 ND that have used hard end points, such as ESRD and mortality, are limited.…”
Section: Introductionmentioning
confidence: 99%